Risk of fracture in patients with Parkinson's disease - Pouwels, S; Bazelier, M; De Boer, A; Weber, W; Neef, C; Cooper, C; De Vries, F (2013)
The aim of the study was to determine fracture risk in incident Parkinson's disease (PD) patients. This study showed that fracture risk assessment may be indicated among patients with PD, in particular when they have recently used selective serotonin re-uptake inhibitors or high-dose antipsychotics, or have a history of fracture, falling, low body mass index (BMI) or renal disease. Introduction: PD is a movement disorder associated with falling and detrimental effects on bone. Both are recognized risk factors for fracture. Therefore, the aim was to determine fracture risk in incident PD patients stratified by treatment, severity, duration of disease and related comorbidities. Methods: We conducted a retrospective cohort study using the UK General Practice Research Database (1987-2011). Each PD patient was matched by age, sex, calendar time and practice to a control patient without history of PD. Results: We identified 4,687 incident PD patients. Compared to controls, a statistically significant increased risk was observed for any fracture (adjusted hazard ratio [AHR], 1.89; 95 % confidence interval [CI], 1.67-2.14), osteoporotic fracture (AHR, 1.99; 95 % CI, 1.72-2.30) and hip fracture (AHR 3.08; 95 % CI, 2.43-3.89). Fracture risk further increased with history of fracture, falling, low BMI, renal disease, antidepressant use and use of high-dose antipsychotics. Conclusion: This study showed that incident PD patients have a statistically significant increased risk of fracture. Therefore, fracture risk assessment may be indicated among PD patients, who, besides the general risk factors for fracture, like increasing age and female gender, have recently used selective serotonin re-uptake inhibitors or high-dose antipsychotics or have a history of fracture, falling, low BMI or renal disease. © 2013 International Osteoporosis Foundation and National Osteoporosis Foundation.